Content Analysis Exercise - Roy, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Select a type of document that has occurred regularly in some other time or place than twenty-first century US. Examples might be newspaper stories, magazine articles, letters, government reports, television shows, songs, etc. The main criterion is that it be repeated, so that the frequency of content has some sociological significance.